Mechanisms of Drug-Induced Mitotic Catastrophe in Cancer Cells - Portugal, Jose; Mansilla, Sylvia; Bataller, Marc (Current Pharmaceutical Design, 2010)
Mitotic catastrophe is a mechanism of cell death characterized by the occurrence of aberrant mitosis with the formation of large cells that contain multiple nuclei, which are morphologically distinguishable from apoptotic cells. Sometimes, mitotic catastrophe is used restrictively to indicate a type of cell death that occurs during or after a faulty mitosis leading to cell death, which takes place via necrosis or apoptosis, rather than a cell death itself. Several antitumor drugs and ionizing radiation are known to induce mitotic catastrophe, but precisely how the ensuring lethality is regulated or what signals are involved is barely characterized. The type of cell death resulting from antitumor therapy can be determined by the mechanism of action of the antitumor agent, dosing regimen of the therapy, and the genetic background in the cells being treated. Wild-type p53 promotes apoptosis or senescence, while mitotic catastrophe is independent of p53. Mitotic catastrophe can be regarded as a delayed response of p53-mutant tumors that are resistant to some damage. In this context, the elucidation of the mechanisms of treatment-induced mitotic catastrophe should contribute to an improvement of the antitumor therapy, because most of the solid tumors bear an inactive p53 protein.
Keywords: apoptosis